Analisis Sosial Ekonomi Pembentuk Tipologi Wilayah Peri Urban Kecamatan Sungai Raya, Kabupaten Kubu Raya - Nana Novita Pratiwi; Agustiah Wulandari; Hukma Zulfinanda (Jurnal Wilayah dan Lingkungan, 2021)
Sungai Raya sub-district is one of a peri-urban areas of Pontianak City as an urban core. As the provincial capital, Pontianak City has a high dynamic of development that has an impact on the development of Sungai Raya Subdistrict as a peri-urban area with direct borders. One of the impacts is the socio-economic aspect. In general, the socio-economic conditions in Sungai Raya District have changed from an agricultural to non-agricultural character. In addition, population growth in Sungai Raya District has also increased over the last five years. It is feared that the development will become uncontrollable. The study aims to determine the typology of the area based on the socio-economic aspects in Sungai Raya District. The method used is a scoring analysis that produces three typologies, namely the primary urban peri, secondary urban peri, and rural peri urban. Based on the results of the analysis, it is known that livelihoods, economic resilience index, growth and population density show a relevant relationship between the conditions of peri-urban areas in characterizing urban and rural characters. This is evidenced by the deviation value of the correlation between these variabels, which is <50%. Furthermore, the scoring analysis showed that 35% of Sungai Raya District (seven villages) were classified as primary peri urban typology, 10% (two villages) were secondary peri urban typology and 55% (eleven villages) were rural peri urban.